Assessing Learning for Leadership A Multimethod Qualitative Evaluation of the 1992 Arizona Leadership Academy - Dereshiwsky, Mary I. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
The Arizona Leadership Academy (ALA) assists school leadership teams in making a positive difference in their schools and communities in order to improve the education of the students of Arizona. Participants focus on schools and communities working together, examine the role of professional growth and development for educators, develop a networking process, address the new roles of leadership within schools including shared decision making and site-based management, and learn and practice facilitation methods to assist in successfully developing and implementing school planning and change. This paper provides a comprehensive evaluation of the Summer 1992 Arizona Leadership Academy. The evaluation is summarized according to major subsections of the survey which was disseminated to participants (N=400) during the fall of 1992 (a total of 67 usable surveys were returned). Findings indicate that the experience was beneficial for the team members and leaders, faculty, and program planners. Some specific strengths noted were the emphasis on team building and interpersonal communication skills, the variety of formal and informal networking opportunities, and its positive influence upon the participants' goals of professional growth. recommendations include planning for a greater proportion of activities devoted to team building and networking opportunities. Appendixes provide a complete copy of the survey, responses to most of the survey items, and summary statistics for demographic items. (LL)
ERIC Note: Paper presented at the Pacific Rim Symposium on Higher Education Evaluation (Hilo, HI, June 2-5, 1993).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Agents; Data Analysis; Educational Change; Educational Improvement; Educational Trends; Elementary Secondary Education; Evaluation Methods; Faculty Development; Inservice Education; Leadership Training; Program Evaluation; School Personnel; Surveys; Arizona Leadership Academy; Speeches/Meeting Papers; Reports, Research; Tests/Questionnaires.